India vision 2020: the report plus background papers - Gupta, S.P. (Chairman) (New Delhi, 2007)
Issues pertaining to India$1 (Bs future development are discussed in this report by the Committee on India Vision 2020 and its associated background papers. Covering a wide range of issues$1 (Bfrom employment and finance to women$1 (Bs rights and urbanization$1 (Bthe essays provide a comprehensive look at the concerns facing India and offer some idea as to where the country is headed.s
Keywords: Economic development-India